Hybrid rare-earth-doped silicon-based microlasers using low-loss low-temperature sputtered oxide thin films - Torab Ahmadi, Pooya (My University, 2025)
Silicon and silicon nitride are well-established platforms for advancing photonic integrated circuits (PICs). Although many critical components for PICs are available in standard foundry processes, a major challenge in these platforms is the realization of efficient and cost-effective on-chip lasers. Recent advances in the hybrid integration of rare-earth-doped oxide glasses offer a potential solution for achieving low-cost and monolithic lasers and amplifiers on these platforms. Among various oxide hosts for rare-earth ions, aluminum oxide (Al2O3) and tellurium oxide (TeO2) present attractive optical properties and ease of fabrication, making them suitable candidates for such applications. This thesis investigates the development of hybrid rare-earth-doped microlasers on silicon and silicon nitride photonic platforms, from introducing a new technique for fabrication of high-optical-quality oxide thin films at low temperatures, to developing compact erbium-doped microresonator lasers by monolithically integrating erbium-doped tellurium oxide (TeO2:Er3+) on silicon nitride waveguides. Furthermore, the hybrid integration of rare-earth-doped microdisk lasers into an active silicon microsystem is demonstrated by incorporating on-chip microheaters to enable laser emission spectrum tuning. Chapter 1 provides an overview of on-chip lasers in silicon photonics, focusing on materials and integration techniques explored in this work. Chapter 2 introduces plasma-assisted reactive magnetron sputtering as a reliable and wafer-scale-compatible technique for the deposition of high-quality oxide thin films for near-infrared applications. This method enables the fabrication of these films at low temperatures, which is critical for their integration with temperature-sensitive photonic substrates. Al2O3 and SiO2 thin films deposited using this technique exhibit minimal propagation losses, an important attribute for high-performance photonic devices. In Chapter 3, hybrid TeO2:Er3+-coated microring lasers on the silicon nitride platform are demonstrated. These lasers show very low lasing thresholds and offer a promising approach toward affordable on-chip light sources for the telecom C-band. Chapter 4 provides the details of the integration of thulium-doped tellurium oxide (TeO2:Tm3+)-coated microdisk lasers into an active silicon microsystem. Incorporating on-chip microheaters facilitates active control over lasing amplitude and spectrum in both single and cascaded microdisk lasers. This capability enables laser emission tuning and stable operation, which are essential for applications such as powering multiple lasers on a chip with a single off-the-shelf diode laser. Chapter 5 presents the design considerations and challenges of achieving hybrid erbium-doped lasers on a silicon platform, detailing experimental results and providing insights into potential solutions for future advancements. Finally, Chapter 6 summarizes the key results of this work and proposes future research directions for advancing the integration of on-chip rare-earth-based light sources in silicon photonics.